Polymer-coated urea effects on yield and gaseous loss of nitrogen for planting Chinese cabbage - Lian Xie; Yifei Du; Li Tang; Xujiao He; Wei Ming; Xiangmin Rong; Yong Xie (PLoS ONE, 2025)
The overuse of nitrogen fertilizer in Chinese vegetable fields, while boosting yield, is a major source of environmental pollution, particularly through N 2 O and NH 3 emissions. Optimizing nitrogen management is therefore crucial for reconciling productivity with environmental sustainability. Here, we assessed whether polymer-coated urea (PCU) with reduced application rates could sustain yield while minimizing environmental costs in Chinese cabbage production. Compared to conventional urea (260 kg N ha ⁻ ¹), PCU applications reduced by 0–20% increased nitrogen use efficiency by 47.7–49.9% and did not affect yield, whereas a 30% reduction caused significant yield loss. These PCU treatments also significantly reduced cumulative N 2 O and NH 3 emissions by 43.5–52.7% and 20.7–40.9%, respectively. We therefore recommend a 20% reduction in PCU-N application as the optimal management strategy for sustainable Chinese cabbage production, ensuring high yield with minimal environmental impact.